In the Backyard of the Factory: Gender, Class, Power and Community in Bahia, Brazil - Sardenberg, Cecília Maria Bacellar (1996)
This dissertation reconstructs and analyzes work relations and everyday life of men and women textile workers in a working-class neighborhood, owned by the mill, in the outskirts of the city of Salvador in Bahia. It also traces the transformation of the neighborhood and of the textile mill from 1875 to 1960. It relies on the combined results of six-years of intermittent field research in the community and in-depth interviews and life histories of twenty men and women who had worked in the factory. It is also based on the analysis of data from payroll books and other company records for a sample of 385 employees The study takes a gender perspective and shows that women’s experience of factory work was unlike that of men. Men and women had distinct domains of influence and faced different struggles. Although the factory relied largely on the employment of the women from the community, patriarchal gender relations dominated in the workplace. Not only was the chain of command in male hands, but it was also men who led and took an active role in the local unions and in collective actions centered in the workplace. Industrial and union paternalism was reinforced by a gender ideology that emphasized women’s domesticity. It served to restrict the participation of women in labor organizations and limit their role in union-led strike movements. Women have only vague and inaccurate recollection of the strikes that were effectively organized when they themselves were part of the work force. They also idealize the paternalistic organization of the factory and the owner who put it in place. At the same time, the textile mill’s reliance on a female labor force enhanced the position of women in their household. A right to a house or house lot and a paycheck made other members of the domestic group dependent on her. It resulted on more egalitarian gender relations within the “backyard of the factory” than within the factory itself. It indicates that gender relations, as well as class relations, do not interlock in fixed ways but that they are flexible and fluid, varying according to the sphere where men and women interact. Indeed, whereas in the past women did not take an active role in workplace-based social movements, they are now in the forefront of neighborhood-based movements, leading the present struggles of their community against their former patrons.